ACTR-04. BIOMARK: A PHASE II STUDY OF BEVACIZUMAB BEYOND PROGRESSION FOR NEWLY DIAGNOSED GLIOBLASTOMA: SAFETY, EFFICACY AND PROSPECTIVE BIOMARKER ANALYSIS. (11th November 2019) - Ichimura, Koichi; Nagane, Motoo; Kato, Mamoru; Narita, Yoshitaka; Aoki, Tomokazu; Tanaka, Shota; Mukasa, Akitake; Wakabayashi, Toshihiko; Uzuka, Takeo; Nakamura, Hideo; Arakawa, Yoshiki; Suehiro, Satoshi; et al.
Abstract: BACKGROUND: Clinical benefit of continuing bevacizumab beyond progression is unknown in glioblastomas. A biomarker analysis of the AVAglio trial suggested that proneural subtype of IDH-wildtype glioblastoma patients may receive an OS benefit from a first-line bevacizumab. This study explored biomarkers that may predict survival of glioblastoma patients treated with concurrent irradiation, temozolomide (TMZ) and bevacizumab (BEV) followed by BEV beyond progression (BBP). METHODS: In the primary protocol, newly diagnosed GBM patients aged 20–75 received concurrent TMZ (75 mg/m 2, D1-42), irradiation (2 Gy x 5 QW x6) and BEV (10 mg/kg Q2W x 3) followed by ≤12 4-week cycles of TMZ (150–200 mg/m 2, D1-5) plus BEV (10 mg/kg, D1 and 15) and then 2 or 3-week cycles of BEV monotherapy (15 or 10 mg/kg). Upon PD/recurrence during the primary protocol, the patients were subjected to the secondary protocol with 2-3-week cycles of BEV monotherapy with or without other chemotherapeutic agents (BBP). The primary endpoint was 2-year survival rate in patients receiving BBP. Fresh-frozen tumor specimen were subjected to genome-wide methylation, copy number, expression and mutation analysis. A subset of the control cohort of the AVAglio study was used as BEV-negative control. RESULTS: A total of 94 GBM patients were enrolled at 39 centers between June 2015 and January 2017. Efficacy analyses were based on the full analysis set (FAS) cohort (N=90), excluding non-GBM diagnosis by central review. The median time to PD/recurrence was 453 days in the FAS and 348 days in patients receiving BBP (N=27). The 2-year survival rate (90% CI) was 52.4% (43.3–60.8%) and 28.8% (15.4–43.7%), respectively. The 2-year survival rate in GBM patients receiving BBP was lower than expected (50%). That of proneural and mesenchymal IDH-wt GBM in the biomarker cohort (n=83) were 52.9% (31.7–70.3%) and 56.6% (41.6–69.1%), respectively. A full biomarker analysis will be presented.